Optimization Of Ethanol Production In Yeast Fermentation Process Based On Mixing Time - Mohd. Ismail, Nur Suriani (2007)
For efficient production of ethanol, once fermentation process should have: good ethanol tolerance, rapid fermentation rate (i.e., high productivity), high fermentation efficiency, temperature tolerance, maintenance of high cell viability and etc.